Prevenção e conduta frente aos eventos adversos pós-vacinação: revisão sistemática e construção de fluxogramas - Vasconcelos, Débora Amorim de (2023)
Post-vaccination adverse event is any medical event after immunization, which may or may not have a causal link with the use of immunobiologicals. Nursing is responsible for the practice of vaccination, being fundamental in the prevention of immunization errors and conduct in the face of these events. The study aimed to investigate the scientific evidence and build flowcharts on prevention and nursing conduct in the face of post-vaccination adverse events in primary health care. The research was carried out in two stages, the first being a systematic review registered in PROSPERO using the identifier CRD42022313144 and search in the MEDLINE, LILACS, Embase, CINAHL and Scopus databases. There was the inclusion of studies involving educational interventions with health professionals working in vaccination for the prevention and management of post-vaccination adverse events and observational studies without language and year restrictions. The bias assessment of the studies was performed using the JBI Critical Appraisal Checklist for Quasi-Experimental Studies and the qualitative analysis using the IRaMuTeQ software. The second stage consisted of building flowcharts for the prevention and management of post-vaccination adverse events through an analysis of data extracted from the systematic review and Ministry of Health manuals on the immunization process. A total of six articles met the inclusion criteria of the SR and the studies showed significant postintervention improvements in the professionals conduct in relation to immunization. The assessment of the risk of bias in the studies showed that most have a moderate risk. Qualitative analysis through descending hierarchical classification, four classes emerged with the following nominations: Educational intervention for the proper management of post-vaccination adverse events, educational intervention for the disposal of waste in the vaccine room, educational intervention for the proper maintenance of the network of cold and educational intervention in administration of vaccines. The similarity analysis showed five words with the highest co-occurrence: health, immunization, vaccine, training, technician and the word cloud presented: study, health, immunization, vaccine and training. A total of six flowcharts were constructed and named as follows: Checking and daily preparation of the cold chain to start vaccination, screening in vaccination, preparation, handling and administration of vaccines, conduct after administration of vaccines, conduct in the face of adverse events postvaccination and/or immunization errors and checking and daily preparation of the cold chain for completion of vaccination. The construction of the flowcharts aims to support permanent health education in the immunization process with a focus on the prevention and management of postvaccination adverse events, as they are educational tools from a safe source with synthetic, accessible, updated and easy-to-understand language. It emphasizes the importance of developing educational technologies to raise awareness and help health management and nurses in providing educational strategies in the vaccination context through a critical reflection of the work to promote safe practices in vaccination, since there are few available technologies and that professionals seek knowledge from unreliable sources.